Secondary acute lymphoblastic leukemia, a retrospective analysis from Washington University and meta-analysis of published data. (September 2018) - Ferraro, Francesca; Gao, Feng; Stockerl-Goldstein, Keith; Westervelt, Peter; DiPersio, John F.; Ghobadi, Armin
Highlights: The latency of s-ALL is shorter post chemotherapy compared with radiotherapy or surgery alone. Patients with s-ALL have worse overall survival independent of other known prognostic factors. Allogeneic transplant with myeloablative conditioning does not improve OS due to high TRM. Abstract: Secondary acute lymphoblastic leukemia (s-ALL) is rare and poorly defined and data regarding outcomes post-transplant are lacking. Here, we report a detailed analysis of s-ALL at our Institution. Among 211 eligible patients with ALL from 2006 to 2017, 30 (14%) were defined as s-ALL and the remaining as primary ALL (p-ALL). s-ALL patients were older and had higher incidence of adverse risk factors. Overall response (OR) after induction was not different between s-ALL and p-ALL (79% versus 90% respectively, p = 0.106). S-ALL group had a higher risk of relapse (RFS) and death (RFS HR = 1.93, 95% CI 1.2–3.12, p = 0.007. OS HR: =1.95, 95% CI 1.18–3.23, p = 0.01). In multivariate analysis, the adverse effect of s-ALL on RFS and OS was no longer significant, however a pooled meta-analysis of our and published data indicated that s-ALL is an independent risk factor for lower OS (HR: 1.30, 95% CI: 1.11–1.52, p < 0.01). Myeloablative allogeneic transplantation in s-ALL was associated with lower rates of relapse and higher transplant related mortality without improvement in OS. These data indicate that s-ALL status should be considered for risk- stratification of newly diagnosed ALL. The optimal conditioning regimen for s-ALL patients undergoing allogeneic stem cell transplantation needs to be evaluated in a larger study.